Outcome and treatment-related adverse events of combined immune checkpoint inhibition with flipped dosing in a real-world cohort of 79 patients with metastasized melanoma - Nübel, Charlotte; Amaral, Teresa; Leiter, Ulrike; Flatz, Lukas; Forschner, Andrea (Frontiers in Oncology, 2023)
Combined immune checkpoint inhibition (ICI) with ipilimumab and nivolumab is a widely used treatment regimen for metastatic melanoma with non-resectable metastases. Nevertheless, the standard dose of ipilimumab 3mg/kg bw and nivolumab 1mg/kg bw is associated with a high rate of treatment related adverse events (trAE) (59% grade 3-4). In the CheckMate 511 study, it could be shown that flipped dosing with ipilimumab 1mg/kg bw and nivolumab 3mg/kg bw resulted in a significant reduction of trAE. We have also used this regimen in the clinical setting and report trAE, progression-free survival and overall survival for 79 patients with metastatic melanoma who started combined ICI in the flipped dosing between March 2019 and April 2020. 40 patients started firstline, 50% of whom had elevated LDH baseline. Disease control rate of these patients was 50%. 2year-overall survival rate 67%. 33% of the patients suffered grade 3 or 4 treatment related adverse events. The results of our study correspond very well to the results of the CheckMate 511 study (2year-OS 65%, grade 3-4 immune-related side effects: 35%). Combined ICI with ipilimumab 1mg/kg bw and nivolumab 3mg/kg bw seems to be an equally effective but better tolerated therapy regimen for metastasized melanoma patients, also in a real-world cohort.